Power allocation algorithms in two-hop relaying networks based on optimal energy efficiency - Bao-feng JI; Jia YANG; Yi-dan WANG; Ying HU; Chun-guo LI; Liang SONG (Tongxin xuebao)
The joint source-relay power allocation issue in green dual-hop single antenna relaying systems was investi-gated from the energy efficiency point of view. By considering a practical power consumption model, the optimal algo-rithm in order to satisfy the constraints of system quality of service was proposed. The non-convex problem was con-verted into the convex problem through high power approximation and then the highly complicated optimization problem was solved by deliberately manipulating the Lagrangian function using the properties of the Lambert function. The opti-mal transmit power of the source and that of the relay are derived in the form of analytical expressions based on the maximization of EE with a guarantee of the required spectral efficiency(SE).It is shown that the optimal relay-to-source power ratio is adaptive to the ratio of the instantaneous two-hop channel gains. Numerical simulations have illustrated the effectiveness of proposed scheme.